EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF SCRIPT UNTUK MENINGKATKAN PRESTASI BELAJAR PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Ilham Rahmawati; Cicilia Melinda (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2021)
The low student achievement in social studies topics motivates this research. This is because the teacher's learning process still applies the conventional learning model. So academic performance in social studies topics is low. The Cooperative Script model is very appropriate to improve student achievement in learning process, as this model can encourage cooperation and student activity in mastering lessons to achieve maximum academic performance. The purpose of this study was to examine the efficacy of the script-cooperative learning model to improve social studies for SMP N students in Rokan Hulu Regency. This type of study is a two-group pretest posttest design research experiment. Population and sample were second-year students of SMP N 12 Tambusai Utara. Data collection method through written testing. Type of statistical analysis was using t-test. Results showed that the cooperative learning model of script is more effective than conventional learning model to improve student learning outcomes. This study focuses on the script cooperative learning model to improve student achievement in junior high school social studies subjects. The results of this study can be used as reference material for further research using different variables. Such as a cooperative script learning model to increase student learning activity.